Adherence to recommendations by infectious disease consultants and its influence on outcomes of intravenous antibiotic-treated hospitalized patients - Fariñas María-Carmen; Saravia Gabriela; Calvo-Montes Jorge; Benito Natividad; Martínez-Garde Juan-José; Fariñas-Alvarez Concepción; Aguilar Lorenzo; Agüero Ramón; Amado José-Antonio; Martínez-Martínez Luis; Gómez-Fleitas Manuel (BMC Infectious Diseases, 2012)
Abstract Background Consultation to infectious diseases specialists (ID), although not always performed by treating physicians, is part of hospital’s daily practice. This study analyses adherence by treating physicians to written ID recommendations (inserted in clinical records) and its effect on outcome in hospitalized antibiotic-treated patients in a tertiary hospital in Spain. Methods A prospective, randomized, one-year study was performed. Patients receiving intravenous antimicrobial therapy prescribed by treating physicians for 3 days were identified and randomised to intervention (insertion of written ID recommendations in clinical records) or non-intervention. Appropriateness of empirical treatments (by treating physicians) was classified as adequate, inadequate or unnecessary. In the intervention group, adherence to recommendations was classified as complete, partial or non-adherence. Results A total of 1173 patients were included, 602 in the non-intervention and 571 in the intervention group [199 (34.9%) showing complete adherence, 141 (24.7%) partial adherence and 231 (40.5%) non-adherence to recommendations]. In the multivariate analysis for adherence (R2 Cox=0.065, p=0.009), non-adherence was associated with prolonged antibiotic prophylaxis (p=0.004; OR=0.37, 95%CI=0.19-0.72). In the multivariate analysis for clinical failure (R2 Cox=0.126, p<0.001), Charlson index (p<0.001; OR=1.19, 95%CI=1.10-1.28), malnutrition (p=0.006; OR=2.00, 95%CI=1.22-3.26), nosocomial infection (p<0.001; OR=4.12, 95%CI=2.27-7.48) and length of hospitalization (p<0.001; OR=1.01, 95%CI=1.01-1.02) were positively associated with failure, while complete adherence (p=0.001; OR=0.35, 95%CI=0.19-0.64) and adequate initial treatment (p=0.010; OR=0.39, 95%CI=0.19-0.80) were negatively associated. Conclusions Adherence to ID recommendations by treating physicians was associated with favorable outcome, in turn associated with shortened length of hospitalization. This may have important health–economic benefits and stimulates further investigation. Trial registration Current Controlled Trials ISRCTN83234896. http://www.controlled-trials.com/isrctn/sample_documentation.asp